2000
DOI: 10.1051/forest:2000166
|View full text |Cite
|
Sign up to set email alerts
|

Climatic signals in earlywood, latewood and total ring width of Corsican pine from western France

Abstract: -The influence of climatic factors on the growth of Corsican pine, growing at low elevation on acidic well-drained soils in western France, was evaluated by comparing annual earlywood, latewood and total ring indices with monthly temperature and precipitation data collected at Angers over the period . Latewood formation appeared to be more sensitive to climate than earlywood formation. Pointer years analysis and climatic models showed that summer drought was a major limiting-growth factor in the studied area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
102
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 30 publications
22
102
0
3
Order By: Relevance
“…Our finding of highly significant relationships between tree radial growth of the majority of black pine and summer temperature (negative) and hydrological year (September to June) cumulative precipitation (positive) is consistent with previous results for the Mediterranean (Andreu et al, 2007;Macias et al, 2006;Sarris et al, 2007) and for the same species in other parts of Europe (Leal et al, 2008;Lebourgeois, 2000). Although in our study these relationships were observed along the latitudinal range in the Iberian Peninsula, intra-annual differences were also observed between regions (i.e.…”
Section: Relationship Between Climate and Radial Growthsupporting
confidence: 81%
“…Our finding of highly significant relationships between tree radial growth of the majority of black pine and summer temperature (negative) and hydrological year (September to June) cumulative precipitation (positive) is consistent with previous results for the Mediterranean (Andreu et al, 2007;Macias et al, 2006;Sarris et al, 2007) and for the same species in other parts of Europe (Leal et al, 2008;Lebourgeois, 2000). Although in our study these relationships were observed along the latitudinal range in the Iberian Peninsula, intra-annual differences were also observed between regions (i.e.…”
Section: Relationship Between Climate and Radial Growthsupporting
confidence: 81%
“…The pointer years analysis provides information on an individual year basis and can be considered as a supplement to the calculation of linear regression models [43,48]. The combination of these different procedures gives the most comprehensive dendroclimatological information [30]. In this study, the three methods clearly showed that the radial growth of old sessile oak trees, growing at low elevation on acidic soil in the Forest of Bercé, is mainly controlled by current spring hydric balance and previous autumn conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The pointer years were defined for each ring component as those calendar years when at least 75% of the rings were at least 10% narrower or wider than the previous year. Thus, each pointer year was expressed as a relative growth changes in % [2,30]. Absolute dating was checked by program COFECHA [24] which identifies all locations within each ring series that may have erroneous cross-dating.…”
Section: Sampling Measurements and Computation Of Chronologiesmentioning
confidence: 99%
“…Calculations were done using the routine RESBO in the program PRECONK version 5.11 (written by H.C. Fritts, Laboratory of Tree-Ring Research, University of Arizona). This includes a bootstrap method to assess statistical significance of the regression coefficients in response functions [22,29,48]. In this work, 1000 iterations were computed to estimate the confidence intervals of regression coefficients (P < 0.05).…”
Section: Dendroclimatic Analysismentioning
confidence: 99%